Enhancing food security through reducing Champa rice losses: Assessing the impact of crop moisture and harvesting methods on yield quantity and quality - Jamshid Kyani; Mahmoud Ghasemi-Nejad-Raeini; Afshin Marzban (PLoS ONE, 2025)
Rice is a major staple crop globally, and minimizing harvest-stage losses is essential for improving production efficiency and food security. Among the critical factors in direct combine harvesting, the timing—determined by grain moisture content plays a crucial role in both yield quality and quantity. This study investigated the impact of harvesting methods and grain moisture levels on the quantitative and qualitative losses of Champa rice in Ramhormoz County during the 2019 growing season. A factorial experiment was conducted using a Randomized Complete Block Design (RCBD) with three replications. The factors included three grain moisture levels (13–15%, 23–25%, and 39–41%) and three harvesting methods (manual, rice combine, and grain combine). Results indicated that at low moisture levels, the highest paddy loss (9.53%) occurred with manual harvesting, while the rice combine recorded the lowest loss (2.5%). Conversely, at high moisture levels, grain combine harvesting led to the highest grain breakage (25.66%) and cracked grains (30.66%), whereas manual harvesting resulted in the lowest cracked grain percentage (2.66%). The highest Head Rice Yield (HRY) (83.66%) was achieved at low moisture levels, with manual harvesting yielding the highest average HRY (83.11%). Interaction effects revealed that the combination of manual harvesting and low moisture content produced the highest HRY (86%), while grain combine harvesting at high moisture resulted in the greatest proportion of broken rice (33.66%). These findings highlight the significance of selecting appropriate harvesting methods and timing to reduce losses and enhance rice quality. The type of combine also significantly influenced the mechanical stress on grains. The study recommends using rice combines at lower moisture levels to minimize losses and avoiding grain combine usage under high moisture conditions. Optimizing harvesting practices not only improves rice processing efficiency but also contributes to food security by maximizing yield quality without the need for land expansion.